Religion and Stock Price Crash Risk - Callen, Jeffrey L.; Fang, Xiaohua (Journal of Financial and Quantitative Analysis, 2015)
Abstract This study examines whether religiosity at the county level is associated with future stock price crash risk. We find robust evidence that firms headquartered in counties with higher levels of religiosity exhibit lower levels of future stock price crash risk. This finding is consistent with the view that religion, as a set of social norms, helps to curb bad-news-hoarding activities by managers. Our evidence further shows that the negative relation between religiosity and future crash risk is stronger for riskier firms and for firms with weaker governance mechanisms measured by shareholder takeover rights and dedicated institutional ownership.